2012
DOI: 10.1089/dna.2011.1396
|View full text |Cite
|
Sign up to set email alerts
|

BMP15 Gene Is Activated During Human Amniotic Fluid Stem Cell Differentiation into Oocyte-Like Cells

Abstract: The generation of oocyte-like cells (OLCs) from stem cell differentiation in vitro provides an optimal approach for studying the mechanism of oocyte development and maturation. The aim of this study was to investigate the activation of bone morphogenetic protein 15 gene (BMP15) during the differentiation of human amniotic fluid stem cells (hAFSCs) into OLCs. After 15 days of differentiation, OLCs with a diameter of 50-60 μm and zona pellucida (ZP)-like morphology were observed. Reverse transcription-polymerase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 33 publications
(44 reference statements)
1
37
0
Order By: Relevance
“…Follicle-like structures were successfully differentiated in vitro from hESCs, but these lacked a zona pellucida [26]. Human amniotic fluid stem cells (hAFSCs) were induced to form oocytelike cells in culture in the presence of porcine follicular fluid and expressed EGFP under the BMP15 promoter which was co-localized with ZP2 expression [27]. Studies utilising human cells suggest that the presence of ovarian factors can enhance the ability of stem cells to generate oocytes, however the meiotic and developmental potential of these cells have not been evaluated.…”
Section: Somatic Cell Support For Oocyte Differentiationmentioning
confidence: 99%
“…Follicle-like structures were successfully differentiated in vitro from hESCs, but these lacked a zona pellucida [26]. Human amniotic fluid stem cells (hAFSCs) were induced to form oocytelike cells in culture in the presence of porcine follicular fluid and expressed EGFP under the BMP15 promoter which was co-localized with ZP2 expression [27]. Studies utilising human cells suggest that the presence of ovarian factors can enhance the ability of stem cells to generate oocytes, however the meiotic and developmental potential of these cells have not been evaluated.…”
Section: Somatic Cell Support For Oocyte Differentiationmentioning
confidence: 99%
“…Furthermore, hAFCs expressed DAZL [12], suggesting potential ability to differentiate into germ cell lineage cells. Recently, Cheng et al reported that human amniotic fluid stem cells cultured in medium containing 5% porcine follicular fluid can differentiate into oocyte-like cells [13]. …”
Section: Introductionmentioning
confidence: 99%
“…1). Some evidence has shown that germ-like cells can be generated from somatic stem cells derived from mouse [30,31], sheep [32,33], or human [34][35][36] mesenchymal stem cells; fetal mouse skin [37,38] as well as porcine skin [39][40][41][42] or muscle [42,43] stem cells; and human amniotic fluid stem cells [44,45]. Combined, these studies provide examples in which somatic stem cells differentiated into male or female germ cells in culture.…”
Section: Germ Cell Differentiation From Somatic Stem Cellsmentioning
confidence: 99%